2011
DOI: 10.1371/journal.pntd.0001253
|View full text |Cite
|
Sign up to set email alerts
|

A Screen against Leishmania Intracellular Amastigotes: Comparison to a Promastigote Screen and Identification of a Host Cell-Specific Hit

Abstract: The ability to screen compounds in a high-throughput manner is essential in the process of small molecule drug discovery. Critical to the success of screening strategies is the proper design of the assay, often implying a compromise between ease/speed and a biologically relevant setting. Leishmaniasis is a major neglected disease with limited therapeutic options. In order to streamline efforts for the design of productive drug screens against Leishmania, we compared the efficiency of two screening methods, one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
151
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(174 citation statements)
references
References 43 publications
12
151
1
2
Order By: Relevance
“…When developing in vitro screens to study bioactive molecules for the control of this microorganism, there is a necessity for developing assays to evaluate possible antiparasitic activities against parasites of the genus Leishmania at the different life cycle stages of this pathogen. It is particularly important to develop antiparasitic therapies against the form of the pathogen responsible for the disease in the vertebrate host during the clinical manifestations of the disease [34,35], and is in this way, that in the present study we confirmed the efficacy of a seco-limonoid (triterpene) [18] which exhibits activity against only the intracellular form of the parasite, leading to a decrease and subsequent resolution of the infection in treated infected cells. We demonstrated that this activity is related to an immunomodulatory mechanism of action in which the compound induces an apparent "reactivation" of the "paralyzed" APC caused by the survival mechanisms developed by the pathogen.…”
Section: Discussionsupporting
confidence: 79%
“…When developing in vitro screens to study bioactive molecules for the control of this microorganism, there is a necessity for developing assays to evaluate possible antiparasitic activities against parasites of the genus Leishmania at the different life cycle stages of this pathogen. It is particularly important to develop antiparasitic therapies against the form of the pathogen responsible for the disease in the vertebrate host during the clinical manifestations of the disease [34,35], and is in this way, that in the present study we confirmed the efficacy of a seco-limonoid (triterpene) [18] which exhibits activity against only the intracellular form of the parasite, leading to a decrease and subsequent resolution of the infection in treated infected cells. We demonstrated that this activity is related to an immunomodulatory mechanism of action in which the compound induces an apparent "reactivation" of the "paralyzed" APC caused by the survival mechanisms developed by the pathogen.…”
Section: Discussionsupporting
confidence: 79%
“…De Muylder et al (2011) established a cut-off regarding the specificity of compounds between these two stages of the parasite Leishmania sp. Specificity value > 2 was the cut off point chosen to define a compound as being more active against the intracellular amastigote stage; while a specificity value < 0.4 indicated a more active compound against promastigotes; compounds with specificity values between 0.4 and 2 were considered as being active against both stages.…”
Section: Resultsmentioning
confidence: 99%
“…Until this in vitro/in vivo correlation is complete, we cannot specify the most appropriate in vitro efficacy model for a Leishmania species or a class of compounds. In this regard, we note that de Muylder and others have recently compared the frequency of in vitro hits by using promastigotes, axenic amastigotes, and within-macrophage amastigotes for 909 compounds, 8 and a publication by Zhu and others is also now available. 9 The in vitro experience of de Muylder and others suggested that screening against the promastigote stage of L. donovani, although more suitable for automation, fails to identify all active compounds and leads to numerous false-positive hits.…”
Section: Drug Discovery Algorithmmentioning
confidence: 98%
“…9 The in vitro experience of de Muylder and others suggested that screening against the promastigote stage of L. donovani, although more suitable for automation, fails to identify all active compounds and leads to numerous false-positive hits. 8 In vivo evaluation of potential oral agents for CL agents. In vivo screening and evaluation of chemical agents requires model systems that are efficient and represent the clinical situation (Table 1).…”
Section: Drug Discovery Algorithmmentioning
confidence: 99%